Hubungan Antara Tingkat Harga Diri Tenaga Medis (Self-Esteem) Dengan Tingkat Kepuasan Pasien Yang Menjalani Rawat Jalan Di Puskesmas Jayapura Utara - Muhlis Muhlis; Wigyo Susanto; Betie Febriana; Waluyo Sejati (Jurnal Keperawatan Komplementer Holistic, 2026)
High self-esteem in medical personnel will create confident, optimistic, and self-assured personnel. High self-confidence will enhance professionalism and lead to satisfactory service delivery. This study aims to determine the relationship between medical personnel's self-esteem and outpatient satisfaction at the North Jayapura Community Health Center in Papua, Indonesia. This research method used a quantitative approach with a correlational design. A sample of 30 respondents, consisting of 15 medical personnel and 15 outpatients, was selected using a total sampling technique. The research instruments were the PSQ-8 questionnaire and the Coopersmith Self-Esteem Inventory (CSEI). Data analysis used Point-Biserial Correlation. The results of the hypothesis test showed no significant relationship between medical personnel's self-esteem and patient satisfaction (p = 0.847). The correlation coefficient value was -0.055, indicating a very weak and negative correlation. While medical personnel's self-esteem is not directly related to patient satisfaction, it is an important component of a medical professional's well-being.